2014
DOI: 10.1371/journal.pone.0090020
|View full text |Cite
|
Sign up to set email alerts
|

Syncytiotrophoblast Vesicles Show Altered micro-RNA and Haemoglobin Content after Ex-vivo Perfusion of Placentas with Haemoglobin to Mimic Preeclampsia

Abstract: BackgroundCell-free foetal haemoglobin (HbF) has been shown to play a role in the pathology of preeclampsia (PE). In the present study, we aimed to further characterize the harmful effects of extracellular free haemoglobin (Hb) on the placenta. In particular, we investigated whether cell-free Hb affects the release of placental syncytiotrophoblast vesicles (STBMs) and their micro-RNA content.MethodsThe dual ex-vivo perfusion system was used to perfuse isolated cotyledons from human placenta, with medium alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…As an important placental factor, STBM was initially studied in normal pregnancy and PE by Redman et al at the University of Oxford, then various research teams worldwide are dedicated to this area and have developed the nomenclature of STBM to include terms such as syncytiotrophoblast microvilli [6], syncytiotrophoblast microvillous membrane [11,16,17,19], syncytiotrophoblast microparticles [15], syncytiotrophoblast microvesicles [23], syncytiotrophoblast-derived microparticles [8],and syncytiotrophoblast extracellular vesicles [38,39], etc. Increasing evidence shows that STBM have various functions relevant to PE, but the precise mechanism is not fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…As an important placental factor, STBM was initially studied in normal pregnancy and PE by Redman et al at the University of Oxford, then various research teams worldwide are dedicated to this area and have developed the nomenclature of STBM to include terms such as syncytiotrophoblast microvilli [6], syncytiotrophoblast microvillous membrane [11,16,17,19], syncytiotrophoblast microparticles [15], syncytiotrophoblast microvesicles [23], syncytiotrophoblast-derived microparticles [8],and syncytiotrophoblast extracellular vesicles [38,39], etc. Increasing evidence shows that STBM have various functions relevant to PE, but the precise mechanism is not fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…The shape of microvesicles may be cell-type dependent. EVs (50-600 nm) shed from perfused human placentas were spherical in shape as demonstrated by transmission electron microscopy (Cronqvist et al 2014). The shedding of placental material has been known for many years (Redman et al 2012).…”
Section: Extracellular Vesicles and Their Characteristicsmentioning
confidence: 91%
“…Our own studies have shown that differential centrifugation alone is not sufficient to separate STB exosomes (30-100 nm) from STB microvesicles (100-1000 nm; Cronqvist et al 2014). STBEVs were isolated from medium following dual-placental perfusion taken from normal women at delivery as described in Cronqvist et al (2014).…”
Section: Sources Of Stbevs and Isolation Methodsmentioning
confidence: 99%
“…The C19MC cluster of miRNA is expressed almost exclusively in the placenta (Luo et al 2009), and it was reported that placental exosomes predominately carry this family of miRNA (Donker et al 2012). In an in vitro model of preeclampsia, term placentae that have been perfused with hemoglobin produce microvesicles that showed a down-regulation of miRNA517a/b ( part of the C19MC cluster) (Cronqvist et al 2014), suggesting that changes in the content of nucleic acids in placental vesicles could contribute to the pathogenesis of preeclampsia.…”
Section: Nucleic Acidsmentioning
confidence: 99%